(untitled) (Marketing Journal, 2025)
This article analyzes the concept of eco -marketing strategies in the retail sector. In particular, it examines areas such as sustainable sourcing, eco -friendly branding, and green operations. Furthermore, the economic effectiveness of these strategies is a lso analyzed — based on factors such as increased sales, customer retention, brand equity, and return on investment (ROI). By studying these aspects, the article aims to demonstrate that eco -marketing strategies not only contribute to environmental sustain ability but also ensure financial success for retail companies.